Perkembangan Wakaf Saham dan Regulasinya di Indonesia - Sholihah, Nurlailiyah Aidatus; Fatmah, Nurlaeli (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This paper aims to analyze the development of share waqf in Indonesia and the regulation of legal certainty in the implementation of share waqf. This research method uses qualitative methods with literature study as the approach. Source of data in the form of library publications. The type of data is in the form of written narratives or documents contained in publication sources. Data collection techniques are carried out by tracking the sources of these publications. The data analysis technique is descriptive. This article finds that share waqf in Indonesia has developed from 2019 to 2020 since the idea of ​​​​its presence. This can be seen based on the nominal number of shares waqf in institutions that have obtained legal legality. However, the regulations that form the legal basis for the implementation of share waqf do not yet have rules that specifically regulate share waqf in detail. The rules used are limited to the explanation of cash waqf and general productive waqf.